2023
DOI: 10.2459/jcm.0000000000001487
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia for cardiologists: a clinical approach to the patient

Abstract: Alexithymia literally meaning 'no words for emotions' is a term used in mental health settings to describe people who have difficulties in identifying and verbalizing their emotional states. There is evidence in the literature that this personality trait may influence negatively the illness behavior when an acute coronary event occurs. In fact, people with high alexithymia are more likely to experience wrong appraisal and interpretation of symptoms, and because of their difficulty in describing feelings to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Peter Sifneos coined the term, which means "no words for mood" to describe a cluster of cognitive and affective characteristics, including "operational thinking", initially observed among patients with psychosomatic diseases [7]. Several recent studies have demonstrated an important relationship between alexithymia and psychiatric disorders, drug abuse, personality disorders, and various medical diseases [8][9][10][11]. Currently, the frequency of alexithymia ranges between 9 and 23% in the general population, according to several studies [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Peter Sifneos coined the term, which means "no words for mood" to describe a cluster of cognitive and affective characteristics, including "operational thinking", initially observed among patients with psychosomatic diseases [7]. Several recent studies have demonstrated an important relationship between alexithymia and psychiatric disorders, drug abuse, personality disorders, and various medical diseases [8][9][10][11]. Currently, the frequency of alexithymia ranges between 9 and 23% in the general population, according to several studies [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%